Emotional Eating and Stress in College Students: A Meta-Analysis Study - Nihayatul Faizah; Eny Purwandari (People and Behavior Analysis, 2025)
This study fills a knowledge gap regarding the relationship between emotional eating and stress in college students, which has not received adequate attention and there have not been many studies that examine the relationship between these two variables in the context of college students. Stress that cannot be managed properly will lead to emotional eating behavior, which, in the future, can have both physical and mental effects on the sufferer; therefore, this research is needed. This study aimed to determine the effect of emotional eating on stress and to detect variations among studies using meta-analysis techniques. This study hypothesizes that there is a significant relationship between emotional eating and stress in university students. This study analyzed 9 primary studies using the keywords "emotional eating, stress, college" and "emotional eating, stress, adolescent" involving a total sample of n=3005 published in various journals and selected based on specific eligibility criteria. The analysis was conducted using VOSviewer to determine the distribution of publication variables and the PRISMA flow for reviewing the articles obtained in 9 studies. The meta-analysis was conducted using JASP software. The heterogeneity test results showed that the 9 studies were heterogeneous with a p-value <0.001; Q = 27,351. The mean effect size analysis results revealed a significant positive correlation between emotional eating and stress of 0.274 and included in the low category. The results of this meta-analysis are reliable because there is no publication bias and the results can be scientifically validated. This study has several limitations. First, there were only 9 studies analyzed, so the data obtained could have been more extensive. Second, changes in eating patterns based on emotions and responses to stress vary with time and geographical location. Meta-analyses include studies from different times or places that face difficulties in consistently evaluating changes.